Adaptasi Pertanian dalam Menghadapi Perubahan Iklim: Peluang Dan Tantangan - Taufiq Ihsan; Vioni Derosya (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Climate change is reported to have huge potential impacts on global agriculture, which vary by geographical region, crop or livestock type, and by the nature of the climatic changes. This paper reviews the relevant literature to determine how the economic impacts of climate change on the agricultural sector are compounded and specified at the regional level. The results show that rising temperatures generally reduce crop yields, and that the negative effects can sometimes be offset by increased precipitation. The winners and losers of climate change will vary geographically, but net yield losses are more likely in warmer semi-arid regions. This review also covers some of the methods used to assess the economic impacts of climate change on agriculture, such as experimental and cross-sectional studies and the Ricardian approach - each with its strengths and limitations. It also discusses the need for mitigation and adaptation strategies in the face of the challenges posed by climate change and highlights the need for context-specific approaches. The review concludes with a call for further research into rainfall patterns, the duration of natural disasters and the specific impacts of climate change on crop yields and nutrition.